(untitled) (Research, Society and Development, 2021)
Introduction: Polycystic Ovary Syndrome (PCOS) is an endocrine disorder, heterogeneous, whose etiology is unknown and with high phenotypic variation. The first-line treatment for this disease is physical training. Objective: To evaluate two types of physical training, concurrent and aerobic, in obese and overweight women with PCOS. Methodology: This is a clinical, analytical, prospective, controlled and randomized study, using training protocols in the "before-after", where aerobic training was used, which is the use of oxygen as an energy source, and the concurrent training, which is the use of strength training and aerobic training. Thirty women were selected, of which 14, approximately 47% of the total number of patients participated in the program, aged between 18 and 40 years with obese and/or overweight PCOS, and subsequently randomized to Group I and Group II: the evaluation of the effects of the two training sessions, concurrent and aerobic, on anthropometric, metabolic and hormonal parameters was made through specific protocols for aerobic and concurrent training. The IBM SPSS version 27.0 program was used for statistical analysis. The normal distribution of data was performed using the Shapiro-Wilk test, and to assess the significant change in the post-intervention variable, the paired t-student test was applied. Results: There were statistically significant differences in the variables studied in the anthropometric parameters in Concurrent Training (TC) and Aerobic Training (AT) such as weight, Body Mass Index (BMI), metabolic age and fat. the majority (42.86%) had higher education, (57.14%) declared themselves black and (100%) were sedentary. Comparing the AT and CT relative to anthropometric parameters, the groups were homogeneous, with difference only in thigh D(P=0.038). Conclusion: Competitive and aerobic physical training performed three times a week for three months significantly reduce several parameters such as weight, BMI, fat and metabolic parameters. The effectiveness is similar in the anthropometric parameters of both physical training, concurrent and aerobic.